Ranking the Factors Affecting the Retention of Human Capital with Organizational Support Approach (Case study: Mashhad University of Medical Sciences) - Mahshid Mojtahedi; NaziaSadat Naseri; Farideh Hashemian Nejad; Fatemeh Heshmati Nabavi (Mashhad University of Medical Sciences, 2022)
Background: In our country, one of the first steps to recognize the problems of employee retention, both for policy makers and organizations is to understand the factors expected by employees, so the purpose of this study was to rank the factors affecting the retention of human capital with organizational support approach.Method: The present study was applied in terms of purpose and the mixed method (qualitative-quantitative) has been used. The statistical population in the quantitative part included the faculty members of Mashhad University of Medical Sciences in the academic year of 2018-2019 that 272 people were selected by stratified sampling method, appropriate to the size of each group, and in the qualitative section, the ideas of 32 experts were used by Delphi technique. The research material was a researcher-made questionnaire extracted from the qualitative section which validity was confirmed by experts and its reliability was calculated higher than 0.7, using Cronbach's alpha coefficient in all Delphi stages. The final questionnaire with 8 dimensions and 53 components was administered among the sample and the data were analyzed using SPSS24 software.Results: The results showed that both organizational factor (coefficient = 0.94) and personal factor (coefficient = 0.83) had the most impact among the factors and environmental factor (coefficient = 59) had the least impact among the factors, with emphasis on organizational support.Conclusion: Managers of medical universities should expand the supportive environment and create promotion opportunities in the university, which requires planning and simultaneous attention to all factors of human capital retention, especially through the perceived organizational support by creating trust, confidence and communication in the university environment.